Comparison Of Cascaded H-bridge Inverters for Harmonic Mitigation Considering Various Loads - Suresh Natarajan; R. Samuel Rajesh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper compares the reduction of harmonics in various level cascaded H-bridge inverters. The switching angles for the cascaded H-bridge inverter were calculated by evolutionary optimization technique. Fourier analysis is used to determine the switching angles for the desired electrical parameters. Lower order harmonics such as third, fifth, seventh, ninth and eleventh order harmonics were taken into consideration to reduce the total harmonic distortion. Simulation was done for thirteen, fifteen and seventeen level cascaded H-bridge inverters using Matlab. Total harmonic distortion of voltage and current for R, RL and  Motor load were analyzed.